Filipino provincial youth’s consumption of K-pop and its effects - Justin Ronan S. Punzalan; Janina V. Luga; Karla Auria S. Galeon (Universitas PGRI Madiun, 2023)
Korean Wave or Hallyu is the popularization of the South Korean culture all over the world. Through the use of Cultural Proximity, and Uses and Gratification Theories as guide, this research was able to understand the reasons of Filipino provincial youth’s consumption of K-pop music, video, and merchandise, and its subsequent effects to their cultural capital, values, and linguistic, and artistic choices. The data from the self-report of 300 Ilokano 3rd and 4th generation K-pop fans, aged 18 to 30 years old was analyzed using correlation analysis.The respondents are mainly Gen Zs, 3rd generation K-pop fans, and females. The top three (3) most popular stans are Blackpink, BTS, and Twice. The findings show their active consumption of Korean popular music, videos and merchandise. Further, varying degrees to which the respondents cite the following reasons as justification of their K-pop consumption are recorded: for entertainment, establishment and reinforcement of social relationships, and personal identity, and surveillance of the characteristics and trends of the South Korean culture. Reasons for music consumption registered a positive significant relationship with cultural capital, negative significant relationship with values and aesthetic, and no relationship with linguistic. All components of effect documented direct relationship will all of the reasons for K-pop video consumption, except values and diversion with no significant relationship at all. Reasons for merchandise consumption have a positive significant relationship with cultural capital, and the linguistic, and aesthetic effects. This study forwards the importance of both traditional and new media in fostering intercultural communication and globalization